Sociophonetic Analysis of the Characters' Speech in "Troubled Blood" by R. Galbraith - Clara Herlina Karjo (Ranah: Jurnal Kajian Bahasa, 2022)
British English has several regional varieties for almost every English county, e.g. Yorkshire, Lancashire, Cornwall, and so on. Each dialect can be distinguished by distinct vocabularies and pronunciation; for example the Cockney dialect use the glottal stop [?] instead of alveolar stop [t] in words like butter and bitter, so they are pronounced as [bΛ?ər] and [bɪ?ər]. These distinctive dialects’ pronunciation can be identified easily in spoken interaction, but it would be more problematic if it was represented in written text, such as in a novel. This paper attempts to analyse the distinguishing features of six intra-national varieties of British English found in the detective novel ‘Troubled Blood’ by Robert Galbraith, which is a pseudonym of J.K. Rowlings. The data for this study were taken from the speech samples of six characters from six regional dialects: Irish, Cornish, Scottish, Cockney, Eastender, and Essex. The speech samples data were extracted from the chapters in which the detective (Strike) or her partner (Robin) conversed with the chosen characters whose language backgrounds were stated clearly in the novel. The data were analysed by transcribing the speech samples phonetically, then from the transcriptions, phonetic features of each regional variation were identified using the theories of sociophonetic and regional variations. The interpretation of the sounds was based on the standard British English pronunciation. Results showed that a woman with East End dialect had some characteristics such as omission of initial h-sound, as in ‘appens, ‘ad, ‘eadaches, while a Scottish dialect was identified by the use of ‘havenae’ for ‘have not’. These results indicate that regional dialects or variations can be represented accurately in written text. Yet, it also suggests that the writer should have ample knowledge of each dialect to be able to represent distinctive variations in their writing.  AbstrakBahasa Inggris British memiliki beberapa variasi regional untuk hampir setiap wilayah Inggris, misalnya Yorkshire, Lancashire, Cornwall, dan sebagainya. Setiap dialek dapat dibedakan dengan kosakata dan pengucapan yang berbeda; misalnya dialek Cockney menggunakan glottal stop [?] alih-alih alveolar stop [t] dalam kata-kata seperti ‘butter’ dan ‘bitter’ sehingga diucapkan sebagai [bΛ?ər] dan [bɪ?ər]. Pengucapan dialek yang khas ini dapat diidentifikasi dengan mudah dalam interaksi lisan, tetapi akan lebih bermasalah jika direpresentasikan dalam teks tertulis, seperti dalam novel. Makalah ini mencoba menganalisis ciri-ciri pembeda dari enam dialek intra nasional Bahasa Inggris British yang ditemukan dalam novel detektif 'Troubled Blood' karya Robert Galbraith, yang merupakan nama samaran dari J.K. Rowling. Data untuk penelitian ini diambil dari sampel tuturan enam karakter dari enam dialek daerah: Irlandia, Cornish, Skotlandia, Cockney, Eastender, dan Essex. Data sampel ujaran diambil dari bab-bab di mana detektif (Strike) atau pasangannya (Robin) berbicara dengan karakter terpilih yang latar belakang bahasanya disebutkan dengan jelas dalam novel. Data dianalisis dengan mentranskripsikan sampel ujaran secara fonetis, kemudian dari transkripsi tersebut diidentifikasi ciri-ciri fonetik masing-masing variasi regional dengan menggunakan teori sosiofonetik dan variasi regional. Penafsiran suara didasarkan pada pengucapan bahasa Inggris standar. Hasil penelitian menunjukkan bahwa seorang wanita dengan dialek East End memiliki beberapa karakteristik seperti penghilangan bunyi h awal, seperti pada 'appens, 'ad, 'eadaches, sedangkan dialek Skotlandia diidentifikasi dengan penggunaan 'havenae' untuk 'have not' . Hasil ini menunjukkan bahwa dialek atau variasi daerah dapat direpresentasikan secara akurat dalam teks tertulis. Namun, hal itu juga mensyaratkan bahwa penulis harus memiliki pengetahuan yang cukup tentang setiap dialek untuk dapat mewakili variasi yang berbeda dalam tulisan mereka